2012
DOI: 10.2478/v10295-012-0030-7
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Effects of Winter Legumes on Germination and Seedling Indicators of Various Summer Cereals

Abstract: In the present study, the putative allelopathic potential of aqueous extracts (10 % w/v) of three legumes, i.e. alfalfa, berseem and brassica spp., including distilled water treatments as check were evaluated on germination and early seedling growth indicators of rice, sorghum and millet under laboratory conditions. The treatments were compared in completely randomized design with factorial arrangements in four replications. The recorded observations clearly indicated that the germination process and seedling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Leaf-extracts were, invariably, the most inhibitory plant component, independent of the growing season and phenological stages. Leaf extracts of cluster bean (Cyamopsis tetragonoloba L.) and mung bean (Vigna radiata L.) were also the most allelopathic plant component (Ayub et al 2013). For milk peas (Galactica pendula Pers.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf-extracts were, invariably, the most inhibitory plant component, independent of the growing season and phenological stages. Leaf extracts of cluster bean (Cyamopsis tetragonoloba L.) and mung bean (Vigna radiata L.) were also the most allelopathic plant component (Ayub et al 2013). For milk peas (Galactica pendula Pers.…”
Section: Discussionmentioning
confidence: 99%
“…Rice’s allelopathy has been thoroughly examined, and a wide variety of rice types have been proven to hamper the development of various plant species during co-cultivation [ 19 ]. When looking at the behaviour of target crops, it has been observed that rice root and shoot growth are the most sensitive to the stress imposed by allelochemicals [ 20 ]. Extracts from the jungle rice shoot have shown a greater inhibitory effect on root length and seedling dry weight, according to Sitthinoi [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The toxic chemicals released into the soil during breakdown of the residues may cause severe inhibition to germination, however, the concentrations phytotoxins decline as decomposition proceeds [3,6]. The chemicals released alter the plant environment which may result in either poor crop germination or reduced growth [7] and the seeds allowed to germinate in such environments require more time for germination [8]. Lertmongkol et al [9] reported that continuous cropping of mung bean led to plant growth inhibition by between 10 to 25% of successive crop growth.…”
Section: Introductionmentioning
confidence: 99%